What heaven looks like comments on a strange wordless book - Elkins, James 1955- (Laboratory Books, 2017)
"Somewhere in Europe - we don't know where - around 1700. An artist is staring at something on the floor next to her worktable. It's just a log from the woodpile, stood on end. The soft, damp bark; the gently raised growth rings; the dark radial cracks - nothing could be more ordinary . But as the artist looks, and looks, colors begin to appear - shapes - even figures. She turns to a sheet of paper and begins to paint. Today this anonymous artist's masterpiece is preserved in the University of Glasgow Library. It is a manuscript in a plain brown binding, whose entire contents, beyond a cryptic title page, are fifty-two small, round watercolor paintings based on the vision she saw in the ends of firewood logs. This book reproduces the entire sequence of paintings in full color, together with a meditative commentary by the art historian James Elkins. Sometimes, Elkins writes, we can glimpse the artist's sources - Baroque religious art, genre painting, mythology, alchemical manuscripts, emblem books, optical effects. But always she distorts her images, mixes them together, leaves them incomplete - always she rejects familiar stories and clear-cut meanings. In this daring refusal to make sense, Elkins sees an uncannily modern attitude of doubt and skepticism; he draws a portrait of the artist as an irremediably lonely, amazingly independent soul, inhabiting a distinct historical moment between the faded Renaissance and the overconfident Enlightenment. What Heaven Looks Like is a rare event: an encounter between a truly perceptive historian of images, and master conjurer of them." -- front cover inside flap
Includes bibliographical references (pages 119-122) and index
Keywords: Opera magica naturalis; Illustration; Jenseitsglaube; Vision; Opera magia naturalis / 1700-1799; Watercolor painting / 18th century; Art, European / 18th century; Heaven in art; Watercolor painting